GAMBARAN PENGETAHUAN SIKAP DAN PERILAKU MASYARAKAT TENTANG JAMBAN SEHAT DI RW 07 DESA PANGEMPON KECAMATAN KEJOBONG KABUPATEN PURBALINGGA TAHUN 2023 - Siti Marfungah; Joko Malis Sunarno; Bayu Suseno (Unit Penelitian dan Pengabdian Masyarakat Politeknik Banjarnegara, 2023)
Pangempon Village RW 07 has a total of 1,548 households, the number of households that already have permanent healthy latrines is 11.46%, semi-permanent healthy latrines are 0.41% and communal latrines are 3.62%. However, there are still 7.43% who do not have access to healthy latrines. The purpose of this study was to determine the description of knowledge, attitudes and behavior of the community about healthy latrines, characteristics (age, gender, education, occupation), availability of clean water, and ownership of healthy latrines. This type of research is descriptive research with univariate analysis, the sample in this study was 42 families with simple random sampling technique. The results showed that the characteristics of respondents in Pangempon Village RW 07 were mostly aged 36-45 years (33.3%), the majority of gender were female (78.6%), the majority of education levels were elementary school (50.0%), the majority of employment levels were as farmers (42.9%). As many as (61.9%) had good knowledge and (38.1%) had sufficient knowledge. Respondents’ attitudes had 100% positive attitudes. As many as (97.6%) respondents already had positive behavior and (2.45%) had negative behavior. For the availability of clean water for 24 hours owned by respondents has been fulfilled (100%). As many as (71.4%) have healthy latrines and (28.6%) do not have access to proper sanitation healthy latrines and septic tanks. The overall conclusion is that the majority of respondents in Pangempon Village RW 07 have access to proper sanitation for healthy latrines (71.4%), the level of knowledge, attitudes and behavior of respondents about healthy latrines is mostly good, the advice given is counseling/ information from community leaders who understand about healthy latrines and health workers routinely and continuously.